Design Of Santri Admission Portal Admission Portal With E-Santri System - Saepul Millah, Rd. Imam (CV. Generasi Intelektual Digital, 2024)
The development and implementation of the e-Santri portal system for new student admissions at As-Syafi’iah Islamic Boarding School has significantly improved the efficiency and accuracy of the registration process. By utilizing modern web technologies such as Express.js and Laravel, the system automates administrative tasks, enhances data consistency, and simplifies the process for both administrators and prospective students. The system supports real-time data synchronization and includes a conflict resolution mechanism to ensure data integrity. Performance testing showed the system's ability to handle high traffic and large volumes of student registrations, making it scalable for future growth. Feedback from users highlighted the system's intuitive interface and ease of use. This research contributes to the digital transformation of educational institutions, demonstrating how web-based registration portals can streamline administrative processes and improve operational efficiency.